PENGARUH KUALITAS LABA TERHADAP ASIMETRI INFORMASI DAN BIAYA EKUITAS - Sulaiman, Agung Putra; Lasdi, Lodovicus; Harimurti, Yohanes (Widya Mandala Surabaya Catholic University, 2014)
Investor will submit their investment when rate of return is exceeding required cost of equity. Cost of equity is defined based on various information, one of them is earning information. Earning information with good quality will be more relevant for influencing investor decision making. In the other side, Lambert, et al. (2011) found that information asymmetry related to cost of capital, which is included cost of equity, and Bhattacharya, et al. (2011) found that earning quality related to information asym-metry. Based on these findings, it supposed to be direct relation from earning quality to cost of equity and indirect relation through information asymmetry. The purpose of this quantitative research is find empirical evidence for examine and analyze mediated relation from earning quality to cost of equity through information asymmetry. The research object is manufacturing companies that is listed in Indonesian Stock Exhange in 2009. Sample of this research is 64 companies that is selected using purposive sam-pling technic. The hypothesis examination is using path analysis technic. The result of this research shows that there is no mediated relation from earning quality to cost of equity through information asymmetry. This result can be caused by some circumstances which is information asymmetry don’t support mediated relation from earning quality to cost of equity, or difference of sample or research period, or there is a difference of Indonesia stock market characteristic compared to other, or there is a difference of investor behaviour. In addition, another finding that consistent with Bhattacharya, dkk. (2012) which is direct relation is stronger compared to indirect relation, moreover in this research indirect rela-tion isn’t supported by reliable statistic evidence.